M&A deal initiation: the case of the unwelcome suitor. Issue 4 (6th August 2018) - Davis, Frederick; Walker, Thomas; Zhou, Linyi
Abstract : Purpose: Within the context of mergers and acquisitions, the purpose of this paper is to clarify the relationship between the deal initiator and various outcomes of the deal, particularly in consideration of the cash position of the acquiring firm. Design/methodology/approach: Using hand-collected deal initiation data from various filings on the Securities Exchange Commission EDGAR online database, this paper performs a series of event study analyses, multivariate analyses, a Heckman two-step estimation procedure, and an instrumental variable approach to examine merger outcomes. Findings: This paper finds that many merger and acquisition (M&A) outcomes (target and acquirer announcement returns, acquirer long-run returns, premiums, and the method of payment) are significantly related to deal initiation, particularly in consideration of the cash position of the acquiring firm. Overall, evidence is seen as consistent with the theory that "lemons" selectively approach cash-rich acquirers, often to the acquirers' detriment. Originality/value: This paper finds that target-initiated deals are not necessarily associated with poorer transaction outcomes for targets as contemporaneous studies suggest, and presents the first empirical evidence of M&A outcomes related to the deal initiator which are dependent on the cash position of the acquiring firm.